2005
DOI: 10.1158/0008-5472.can-05-2211
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Endogenous OncogenicV600EB-rafInduces Proliferation and Developmental Defects in Mice and Transformation of Primary Fibroblasts

Abstract: Mutations of the human B-RAF gene are detected in f8% of cancer samples, primarily in cutaneous melanomas (70%). The most common mutation (90%) is a valine-to-glutamic acid mutation at residue 600 (V600E; formerly V599E according to previous nomenclature). Using a Cre/Lox approach, we have generated a conditional knock-in allele of V600E B-raf in mice. We show that widespread expression of V600E B-Raf cannot be tolerated in embryonic development, with embryos dying f7.5 dpc. Directed expression of mutant V600E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
194
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(205 citation statements)
references
References 41 publications
11
194
0
Order By: Relevance
“…Our findings are of particular interest as aberrant b-Catenin signalling and EMT have been implicated as important processes in the metastatic progression of tumours with a high incidence of BRAF V600E mutations such as melanomas, thyroid and colorectal carcinomas (Thiery, 2002). Likewise, as EMT and its opposite process are crucial and tightly regulated events during metazoan development, our finding that B-Raf V600E induces EMT might help to explain the embryonic lethal phenotype of mouse embryos with an induced B-raf V600E allele (Mercer et al, 2005).…”
Section: Regulation Of B-raf Signallingmentioning
confidence: 80%
See 1 more Smart Citation
“…Our findings are of particular interest as aberrant b-Catenin signalling and EMT have been implicated as important processes in the metastatic progression of tumours with a high incidence of BRAF V600E mutations such as melanomas, thyroid and colorectal carcinomas (Thiery, 2002). Likewise, as EMT and its opposite process are crucial and tightly regulated events during metazoan development, our finding that B-Raf V600E induces EMT might help to explain the embryonic lethal phenotype of mouse embryos with an induced B-raf V600E allele (Mercer et al, 2005).…”
Section: Regulation Of B-raf Signallingmentioning
confidence: 80%
“…Expression of B-Raf V600E has been shown to transform fibroblasts and melanocytes as well as to induce haematopoietic dysplasia in mice and invasive melanomas in p53À/À zebrafish (Davies et al, 2002;Ikenoue et al, 2004;Wellbrock et al, 2004b;Mercer et al, 2005;Patton et al, 2005). Likewise, suppression of BRAF V600E expression in melanoma lines abrogates their transformed phenotype (Hingorani et al, 2003;Karasarides et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…So far, only 2 transgenic mouse models with either constitutive 77 or conditional 78 expression of mutant B-Raf have been published. Constitutive expression of the mutant human V600E B-RAF under the control of the bovine thyroglobulin promoter induced goiter and invasive papillary thyroid cancers (PTC) with tall-cell features, which later transitioned to poorly differentiated carcino- mas.…”
Section: Raf Kinases and Mouse Cancer Modelsmentioning
confidence: 99%
“…Pritchard and coworkers applied a Cre/lox strategy to generate a conditional knock-in allele of V600E B-Raf. 78 Ubiquitous expression of V600E B-Raf resulted in embryonic death before E7.5, whereas expression in adult somatic tissues induced hyperproliferation and bone marrow failure. 78 Up to now, 2 Raf-dependent mouse tumor models have been generated that allow a preclinical evaluation of novel therapeutic modalities and potential anticancer drugs.…”
Section: Raf Kinases and Mouse Cancer Modelsmentioning
confidence: 99%
“…Experimental studies with mice harboring a knock-in allele of BRAF mutant kinase revealed that BRAF V600E was able to induce cell transformation and proliferation (Mercer et al, 2005). Hongbin et al developed a BRAF V600E mutant mice lineage, which presented lung adenocarcinomas, histologically resembling human adenocarcinomas (Jemal et al, 2009).…”
Section: Mutationmentioning
confidence: 99%